Measurement of the edge ion temperature in W7-X with island divertor by a retarding field analyzer probe. (17th September 2019) - Li, Y.; Henkel, M.; Liang, Y.; Knieps, A.; Drews, P.; Killer, C.; Nicolai, D.; Cosfeld, J.; Geiger, J.; Feng, Y.; Effenberg, F.; Zhang, D.; et al.
Abstract: Knowledge of the edge ion temperature ( T i ) is important to understand the edge physics in fusion plasmas. The T i edge profile has been successfully measured at W7-X in an island divertor configuration using a retarding field analyzer probe on a reciprocating manipulator. The experimental observations show that in the standard configuration, an ion temperature shoulder at the plasma boundary has been observed near the location where a sudden change of the magnetic field connection length appears in the scrape-off layer (SOL) region. The value of the T i shoulder was observed to be dependent on the edge island structure modified by the control coils, SOL kinetic power, and electron density. A significant reduction and flattening in the edge ion temperature profile has been also observed during the nitrogen seeding from the upper horizontal divertor port. In addition, the edge ion-to-electron temperature ratio has been calculated, which gradually increases with the major radius and decreases with the normalized ion collisionality. An extended two-point model including upstream ion temperature is introduced to understand the experimental measurement.